Analisis Keterampilan Teknik Dasar Sepak Takraw pada Ekstrakurikuler Sepak Takraw Putra di SMAN Kota Pematangsiantar - Tekkun Bancin; Teuku Ryan Rizki; Evitamaria Simbolon; Alfonsus Ferdyn Telaumbanua; Ibrahim Ibrahim; Mawardi Nur (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The purpose of this study was to determine the ability of basic techniques of sepak takraw game in students who take part in sepak takraw extracurricular activities at Pematangsiantar City High School. The design used in this research is descriptive quantitative. The instrument used in this study is a test of skills to play sepak takraw, including tests of sepak mula, sepak sila, sepak kura, heading and smash. The population of this study amounted to 18 people. The sampling technique in this study was a full sampling technique where all members of the population were sampled. The results of this study indicate that students who take part in sepak takraw extracurricular activities at Pematangsiantar City High School have good skills in playing sepak takraw. There are 5 players who are in the high category, 9 players who are in the medium category, 4 players who are in the less category, and no players who are very high or very less.